Study of Age-Related Finger Span and Hand Grip Strength of Adult Female Garment Workers in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Age related hand anthropometry is important for the effective designing of dimensionally compatible hand tools, gloves, machine access spaces and hand-held devices. The present study was designed to measure and compare finger spans and the hand grip strength of both hands of adult female garment workers of different age groups in Bangladesh and to establish correlation between finger spans and the hand grip strength of same hand.Materials and methods: The study was a descriptive, observational and cross sectional in nature with some analytic component; carried out in the Department of anatomy, Chittagong Medical College, Chattogram, from January 2015 to December 2015. A purposive non random convenient sampling was done to select 300 female garment workers, age ranging from 21-35 years. Hand grip strength and 5 finger spans were measured. ANOVA test was performed to correlate of finger spans and hand grip strength of different age groups.Results: Difference of hand grip strength with age showed significant in both hands. Difference of finger spans with age showed non-significant. There was positive correlation between finger spans and hand grip strength of the same hand.Conclusion: Study of age related anthropometric measurements of hand can play an important role to design same workplace, same hand tools, and same access spaces for the hand of the age group (21-35) years of adult female garment workers in Bangladesh and increase the usage of human resources.Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 62-66